Hooked : food, free will, and how the food giants exploit our addictions - Moss, Michael, 1955- (Random House, 2021)
"Everyone knows how hard it can be to maintain a healthy diet. But what if some of the decisions we make about what to eat are beyond our control? Is it possible that processed food is addictive, like drugs or alcohol? Motivated by these questions, Pulitzer Prize-winning investigative reporter Michael Moss began searching for answers, to find the true peril in our food. In Hooked, Moss explores the science of addiction and uncovers what the scientific and medical communities--as well as food manufacturers--already know, which is that food can, in some cases, be even more addictive than alcohol, cigarettes, or drugs. Our bodies are hard-wired for sweets, so food manufacturers have deployed fifty-six types of sugar to add to their products, creating in us the expectation that everything should be cloying; we've evolved to prefer convenient meals, so three-fourths of the calories we get from groceries come from ready-to-eat foods. Moss goes on to show how the processed food industry has not only tried to deny this troubling discovery, but exploit it to its advantage. For instance, in a response to recent dieting trends, food manufacturers have simply turned junk food into junk diets, filling grocery stores with "diet" foods that are hardly distinguishable from the products that got us into trouble in the first place. With more people unable to make dieting work for them, manufacturers are now claiming to add ingredients that can effortlessly cure our compulsive eating habits. A gripping account of the legal battles, insidious marketing campaigns, and cutting-edge food science that have brought us to our current public health crisis, Hooked lays out all that the food industry is doing to exploit and deepen our addictions, and shows us what we can do so that we can one again seize control"--